PENGARUH COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK PENINGKATAN KEPERCAYAAN DIRI SISWA KELAS IX SMP NEGERI 1 BERUNTUNG BARU - Aulina, Melda; Jarkawi, Jarkawi; Susanto, Didi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2018)
The purpose of this study was to determine the level of self-confidence of students before the Cogntive Behavior Therapy CBT approach at STATE 1 Lucky New Middle School. The design of this study uses quantitative research methods with the type of experimental research. Experimental research is defined as a research method used to find the effect of certain treatments on others under controlled conditions. The reason the researchers used this type of research, because it uses treatment (treatment) carried out by researchers. The experimental design used in this study is Pre-experimental designs, because there are still external variables that influence the formation of the dependent variable or self-confidence. The form of experimental design used by researchers was with one-group pretest-posttest. The results showed the level of self-confidence of students in STATE 1 Lucky New Middle School before treatment with the Cogntive Behavior Therapy CBT approach with a low pretest score. The level of confidence of students in STATE 1 Lucky Middle School after being treated with the Cogntive Behavior Therapy approach to CBT with an average result of a high posttest score. The Influence of Cognitive Behavior Therapy (CBT) on increasing self confidence in New Lucky 1 Middle School students. Based on the Wilcoxon Asymp test results. Sig 0.042 <0.05, the results of this study Cognitive Behavior Therapy (CBT) have an effect on the increase in confidence in New Lucky 1 Middle School students. Keywords: Cognitive Behavior Therapy, Self Confidence